The Influence of Product Stock, Location and Store Attempt on Purchase Decisions at Indomaret SM Raja Deblod Sundoro Street Tebing Tinggi City - Tria Meisya Aziti (International Journal of Economics (IJEC), 2023)
This study aims to determine the effect of product stock, location and store atmosphere on purchasing decisions at Indomaret SM Raja Deblod Sundoro Street, Tebing Tinggi City. The effect that we want to know is the direct or indirect effect. This type of research is a replication and development of similar previous studies but with different objects, variables and periods. This study used a sample of 96 respondents. Sampling using the Cochran formula technique. The analytical tool used is multiple linear analysis using the SPSS 25 program. From the results of this test it can be concluded that there is a significant effect between Product Stock (X1) on Purchase Decision (Y), there is no significant effect between Location (X2) on Purchasing Decision (Y), there is a significant influence between Store Atmosphere (X3) on Purchase Decisions (Y).